KAIDAH AL-AMR WA AL-NAHYI - Abdul Kallang (fakultas Ushuluddin dan Dakwah IAIN Bone, 2019)
AbstrakVarious interpretations expressed by our ulalma are only human beings who have to do with which they must follow, the question of the interpretation of the Koran which is very diverse with various methods available in interpreting the Koran. With the existence of the Qur'anic sciences which have been formatted by our predecessor scholars, we only have to develop the method. Sala one method that I want to discuss in the rules of the science of interpretation is the issue of الا مر و النهي in the Qur'an and the application of the tesk and its context in seeing the reality that exists.